2022
DOI: 10.3390/su14095727
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Different Types of Environmental Enrichment on the Performance and Welfare of Broiler Chickens and the Possibilities of Real-Time Monitoring via a Farmer-Assistant System

Abstract: The aim of this study is to evaluate the influence of environmental enrichment on the growth performance, litter and/or air quality as well as animal welfare indicators of broilers. Control groups (CG) and trial groups (TG) were housed under identical conditions during six fattening runs, with the TG having three types of environmental enrichment and a Farmer-Assistant System (FAS). A representative number of 50 birds were weighed and litter samples were taken at d 14, 21 and 28. Additionally, the same broiler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…of the skin. The part of the body where the technopathy is found may indicate the causes in the housing (Spieß et al., 2022a ).…”
Section: Assessmentmentioning
confidence: 99%
“…of the skin. The part of the body where the technopathy is found may indicate the causes in the housing (Spieß et al., 2022a ).…”
Section: Assessmentmentioning
confidence: 99%
“…A combination of elevated platforms, increased distance between food and water, live insects, and barrier perches did not affect footpad dermatitis, hock burn, and gait score in both fast- and slower-growing broilers ( de Jong et al, 2021 ; Guz et al, 2021 ), but positive effects were found on tibial biophysical characteristics in both breeds ( Guz et al, 2021 ). A combination of perches, elevated platforms, and combined structures had a positive effect on footpad dermatitis in fast-growing chickens ( Spiess et al, 2022 ). Under commercial conditions, a combination of peat, lucerne bales, and elevated platforms improved gait score in fast-growing chickens ( Vasdal et al, 2019 ).…”
Section: Environmental Enrichment For Broiler Chickens – Are There Be...mentioning
confidence: 99%
“…De Jong and Gunnink [ 29 ] reported that there was no difference in litter quality between the control and enrichment treatment groups that provided with sawdust bales, perches, and metal chains as pecking objects. Spieß et al [ 30 ] found that enrichment consisting of perches and platforms had no significant effect on litter moisture. Mocz et al [ 31 ] also reported that the enrichment environment consisting of platforms and hay bales did not affect litter moisture.…”
Section: Resultsmentioning
confidence: 99%